The Synthetic Strategy and its Role to developing the Mathematical Creative Thinking Skills - Hind Salem; Azaa Kindi; Maha Mohammad; Zahraa Hamad; Tashtoush, Mohammad (International Journal of Multidisciplinary Sciences and Arts, 2023)
This study aimed to investigate the role of the Synthetic Strategy on the development of mathematical creative thinking skills. The study sample consisted of (46) eighth-grade female students who were divided into two groups: an experimental group of (24) students taught linear equations using the Synthetic strategy, and a control group of (22) students taught using the traditional method. An experimental approach was employed, and a test for mathematical creative thinking was prepared. A pre-test and post-test were administered to both study groups, and their validity and reliability were confirmed. The Synthetic strategy was applied to teach solving linear equations. The results revealed a difference in the level of mathematical creative thinking in favor of the experimental group, and statistically significant differences were found between the mean scores of the two groups in mathematical creative thinking skills, which were attributed to the teaching strategy and in favor of the Synthetic strategy. Finally, the study recommended using the Synthetic strategy to teach linear equation and diversifying teaching strategies. It also suggested conducting further studies and research to explore the impact of different teaching strategies on the development of mathematical creative thinking skills.